2009
DOI: 10.4049/jimmunol.0900873
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-Dependent Modification of IL-12p70 and IL-23 Balance in Dendritic Cells by Ligand Activation of Vα24 Invariant NKT Cells

Abstract: CD1d-restricted invariant NKT (iNKT) cells play crucial roles in various types of immune responses, including autoimmune diseases, infectious diseases and tumor surveillance. The mechanisms underlying their adjuvant functions are well understood. Nevertheless, although IL-4 and IL-10 production characterize iNKT cells able to prevent or ameliorate some autoimmune diseases and inflammatory conditions, the precise mechanisms by which iNKT cells exert immune regulatory function remain elusive. This study demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Interestingly, ligand activation of iNKT cells by DCs results in upregulation of CD40 ligand expression on the iNKT cells, which subsequently can stimulate DC maturation and IL-12 production 4143. Furthermore, a recent study by Uemura et al showed that ligand-activated iNKT cells modify the IL-12p70/IL-23 balance in DCs mainly via the production of both Th1 and Th2 cytokines 44. This suggests that suboptimal stimulatory signals and soluble factors from α-GalCer-activated iNKT cells (eg, IL-2, IFNγ and/or IL-4) can have a reciprocal stimulatory effect on the APCs in our co-culture system, which in turn can be inhibited in the SOCS3-transduced APCs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ligand activation of iNKT cells by DCs results in upregulation of CD40 ligand expression on the iNKT cells, which subsequently can stimulate DC maturation and IL-12 production 4143. Furthermore, a recent study by Uemura et al showed that ligand-activated iNKT cells modify the IL-12p70/IL-23 balance in DCs mainly via the production of both Th1 and Th2 cytokines 44. This suggests that suboptimal stimulatory signals and soluble factors from α-GalCer-activated iNKT cells (eg, IL-2, IFNγ and/or IL-4) can have a reciprocal stimulatory effect on the APCs in our co-culture system, which in turn can be inhibited in the SOCS3-transduced APCs.…”
Section: Discussionmentioning
confidence: 99%
“…IL-12p70 is involved in the induction and amplification of the Th1 response, while IL-23 mediates inflammatory responses, through induction of expansion of Th17 cells (Ortaldo et al 2004). Uemura et al demonstrated that when NKT cells are co-cultured with DCs, NKT cells enhance the IL-12p70 production while downregulating IL-23 production by DCs (Uemura et al 2009). …”
Section: Nkt Cell Subsets and Cytokine Profilesmentioning
confidence: 99%
“…This finding is supported by the previous observation that other factors such as ligands for Toll-like receptors are required for DC-mediated differentiation of IL-17-producing Th cells. [46][47][48] Whether Th polarization is also modified by BPA/Toll-like receptor-stimulated DCs remains to be determined.…”
Section: Bpa Induces Th2 Response Via Dcsmentioning
confidence: 99%